Undergraduate students’ perceptions toward writing Instagram captions in English - Nahda Nafisah Hutasuhut; Sholihatul Hamidah Daulay; Achmad Ramadhan (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
Nowadays, young people significantly are writing online productively. In social media, people offer access to more authentic and engaging writing occasions. One social media platform that provides a writing facility is Instagram. Aside from using Instagram just for entertainment, people have started to use Instagram as a learning medium for many courses, including writing skills. This research aims to describe the students’ perceptions of Instagram as a learning medium and writing Instagram captions in English. The methodology of this research was qualitative research. The participants were ten English Education Department students from the 8th semester at a public Islamic university in Medan, North Sumatra, Indonesia. The data were collected through interviews and analyzed in three ways, i.e. data reduction, data display, and conclusion drawing. The study findings demonstrate that the university students perceived that writing Instagram captions in English could improve their skills in English, make them comfortable, practice their writing skills, and give them chances to reach a wider audience. This study concludes with empirical insights into how EFL educators provide best practices for engaging their students with integrating the advancement of social media platforms in their teaching and learning process.